2017
DOI: 10.1016/j.medici.2018.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variations of MTHFR gene and their association with preterm birth in Korean women

Abstract: Our findings suggested that the MTHFR gene 677 C/T and 1298 A/C polymorphisms might have protective effects for preterm birth in the Korean women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…However, a case-control study nested in a multicenter cohort found MTHFR C677T was positively associated with PTB and LBW in India, in which folate status was not reported. Extremely, very, and moderately PTB showed higher frequency of MTHFR C677T mutation compared to term delivery cases [ 20 ]. A Japanese study suggested that maternal MTHFR C677T, not MTHFR A1298C was independently associated with improvement in infant birth weight in the background of 16.4 nmol/L serum folate [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, a case-control study nested in a multicenter cohort found MTHFR C677T was positively associated with PTB and LBW in India, in which folate status was not reported. Extremely, very, and moderately PTB showed higher frequency of MTHFR C677T mutation compared to term delivery cases [ 20 ]. A Japanese study suggested that maternal MTHFR C677T, not MTHFR A1298C was independently associated with improvement in infant birth weight in the background of 16.4 nmol/L serum folate [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The SCOPE study found no significant gene-nutrient interactions between maternal MTRR A66G, MTR A2756G, and folic acid use, and their association with PTB and SGA [ 42 , 43 ], which aligned with our finding of MTRR and MTR SNPs. Tiwari found that MTRR A66G was not related to PTB on the background of high-level folate, but homocysteine concentration did [ 20 ]. Another nested case-control study carried out by Engel found that MTRR A66G was positively related to PTB in the white population, but not in the black population regardless of folate intake level [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have been conducted to evaluate the association between MTHFR genetic polymorphism rs1801133 and pregnancy outcomes. Some have found that the mutated T allele of MTHFR rs1801133 was associated with a higher risk of adverse outcomes, including spontaneous abortion, premature birth, and stillbirth (2,11,(31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
“…Reduced MTHFR activity has a negative effect on reproductive functions as oocyte and embryo development, endometrial receptivity, embryo implantation, and the maintenance of pregnancy [10,11]. Evidences showed that MTHFR 677C > T is associated with ovarian reserve, implantation failure, pregnancy loss, human subfertility and infertility, oocyte maturation, embryo aneuploid [12][13][14], MTHFR 677C > T mutation is also risk factor for premature ovarian failure [15], recurrent miscarriage and implantation failures [14] preterm birth [16]. However, the role of MTHFR C677T genotype on ART outcomes remained unclear.…”
mentioning
confidence: 99%